A new dimeric diarylpropane from Horsfieldia tetratepala. Issue 2 (17th January 2018) - Du, Shou-Zhen; Kuang, Fang; Liu, Ying; Chen, Ye-Gao; Zhan, Rui
Abstract: Five compounds, including a new dimeric diarylpropane, were isolated from the petroleum ether extract of the twigs and leaves of Horsfieldia tetratepala . The structures of these compounds were elucidated by spectroscopic analysis. Moreover, the antiproliferative activities of these compounds were tested on cancer cell lines, but none is active. Abstract :